Potential mri biomarkers for placental structure and function at 1.5 T. (7th June 2011) - Wright, C; Morris, D; Baker, P; Crocker, I; Gowland, P; Parker, G; Sibley, C
Abstract : MRI provides quantitative indices including relaxation time measurements, T1 and T2, which theoretically relate to placental composition and indices relating to perfusion, measured by Intra-Voxel Incoherent Motion (IVIM); related variables D and D* (coefficients of diffusion and pseudo-diffusion) and f% (the fraction of moving blood per voxel). We hypothesised these indices would be useful in the non-invasive assessment of the human placenta and are related to placental tissue morphology. Methods: 40 (30 normal, 10 fetal growth restriction (FGR)) women underwent MRI examination (1.5 T) between 20 and 41 weeks. Placental relaxation times and IVIM measurements were acquired from a mid-depth placental region. Fixed embedded sections of these placentas, collected at delivery were stained and subjected to stereological analysis of morphology. Results: Placental T1 and T2 show a significant negative correlation with gestation in normal pregnancy (p=0.01, 0.03, n=30), whereas IVIM parameters were unchanged (n=10). In the group as a whole, significant correlations were observed between f% and placental fibrin volume and capillary surface area (p=0.02, 0.03, n=6). In the group as a whole, there were no correlations between morphological features and relaxation times (n=19), D or D*(n=6). However, in a subset of pregnancies scanned within a week of delivery, a significant correlation was observed between placental fibrin volume and T2 (p=0.02, n=7). Discussion: The correlations between MRI indices and morphological variables support that these indices may be useful in non-invasive assessment of placental morphology. Ultimately, such indices might be useful in FGR, where alterations in placental morphology are observed.